The Challenges of Diagnosing, Managing, and Preventing Pediatric Delirium - Juliana Patrícia Chaves de Almeida; Yu Kawai; Arnaldo Prata-Barbosa; Roberta Esteves Vieira de Castro (Children)
Pediatric delirium (PD) is an acute neuropsychiatric syndrome marked by fluctuating disturbances in attention and cognition, frequently observed in pediatric intensive care units (PICUs) and associated with increased morbidity, mortality, and long-term cognitive impairment. Despite its clinical significance, PD remains underdiagnosed due to challenges inherent in assessing consciousness and cognition in children at varying developmental stages. Several bedside tools have been developed and validated in recent years, including the Cornell Assessment of Pediatric Delirium (CAPD), PreSchool Confusion Assessment Method for the Intensive Care Unit (psCAM-ICU); Pediatric Confusion Assessment Method for the Intensive Care Unit (pCAM-ICU), and Sophia Observation Withdrawal Symptoms—Pediatric Delirium Scale (SOS-PD), enhancing early recognition and management of PD in critically ill children. This narrative review explores the historical background, epidemiology, risk factors, pathophysiology, clinical subtypes, diagnostic tools, and current prevention and treatment strategies for PD from newborns to 21 years old. The screening tools available and the integration of non-pharmacological interventions, such as environmental modifications and family-centered care, as well as cautious and selective pharmacological management, are emphasized in this review. Early identification and targeted interventions are essential to mitigate the adverse outcomes associated with PD.